Astrocytic abnormalities in brain-specific Cacna1c-deficient mice: Implications for BBB impairment in neuropsychiatric diseases associated with CACNA1C mutations - Yeojung Koh; Maria Noterman-Soulinthavong; Anusha Bangalore; Uapingena P. Kandjoze; Zea Bud; Kamryn L. Noel; Hami Lee; Kathryn Franke; Coral J. Cintrón-Pérez; Anjali M. Rajadhyaksha; Eric B. Taylor; Andrew A. Pieper (Channels)
Intronic genetic variants within the CACNA1C gene, which encodes the pore-forming alpha 1c subunit of the Cav1.2 L-type calcium channel, are significant risk factors for a multitude of neuropsychiatric disorders. In most cases, these intronic SNPs have been associated with reduced CACNA1C expression. Here, we demonstrate that targeted genetic deletion of Cacna1c in mouse brain leads to increased astrocyte reactivity, increased expression of aquaporin 4 (AQP4) in astrocytes adjacent to the blood–brain barrier (BBB), and neuroinflammation, including changes in the levels of brain chemokines and inflammatory cytokines. Astrocytes are vital for maintaining BBB integrity, with AQP4 predominantly expressed in astrocytic endfeet where it regulates water balance in the brain. This function is critical to brain health, and deterioration of the BBB is a major feature of virtually all forms of neuropsychiatric disease. Our results highlight a previously unrecognized role for CACNA1C in astrocytes at the BBB, which could be a major factor in how intronic CACNA1C SNPs broadly increase the risk of multiple forms of major neuropsychiatric disease.